Marketing Strategy Analysis Using SWOT Analysis Method - Dewi Margaretha Prabowo; Iriani Iriani (Yayasan Riset dan Pengembangan Intelektual, 2024)
Currently, drinking coffee has become an integral part of the millennial lifestyle. This trend has led to a proliferation of coffee shops, especially in Surabaya. At the heart of Surabaya is Kota Kopi Ambengan, a modern cafe with a unique vintage charm. However, Kota Kopi has experienced a decline in sales turnover over the past few years. The current marketing strategy needs to be reevaluated. This study aims to develop a strong marketing strategy for Kota Kopi. The research employs the SWOT method to analyze the cafe's internal and external factors, including Strengths, Weaknesses, Opportunities, and Threats. By determining the weight and rating of these factors using the IFAS and EFAS matrices, the cafe's position relative to its competitors and potential strategies are identified using the grand strategy matrix. The internal and external factor weighting scores are both 4,000. According to the grand strategy matrix, Kota Kopi's position in quadrant I suggests it should adopt aggressive strategies. Recommended strategies include modernizing the cafe's interior while maintaining its vintage feel, ensuring product safety and cleanliness, enhancing hygiene in food and beverage production, and offering exclusive incentives to nearby office workers and high school students.